Perancangan Desain UI/UX untuk Aplikasi Sewa Sawah Online Di Desa Tanjungsari Kabupaten Jember Menggunakan Metode User Centered Design (UCD) - Endra Rahmawati; Norma Ningsih (STMIK YADIKA BANGIL, 2021)
Abstract : This study aims to design the user interface design of the Online Rice Field Rental Application in Tanjungsari Village, Jember Regency. The design of this application is expected to helpprogrammers to build an application that is useful for rice field owners and farmers in the village in managing rice fields that are rented directly. This is because some of the rice field owners in thevillage are residents who come from outside the city and own agricultural land or rice fields in the area, but cannot manage it so many are rented out to local farmers to be processed and planted withsecondary crops. The process of renting rice fields in the village usually takes place conventionally by telephone, coming directly to the house of the owner of the fields, or through the services of anintermediary. The rental agreement is sometimes not made in writing, only based on mutual agreement within a certain period of time (annually). To deal with these problems, an alternativesolution is needed that can create an online rice field rental application interface designed using the User Centered Design (UCD) method, focusing on the user's main needs. The design of this onlineapplication for rice rental has four main features, namely the list of agricultural land/rice fields, online rental transactions (direct rental or brokerage services), verification of the rice leaseagreement, and payment of rice leases. The test results using usability testing show that 87.3% of users can accept the interface design of this Sawah Rental Application. On the other hand, the resultsof the 5 second testing can give a good impression on customer interest, especially on the design of the List of Agricultural Land/Paddy fields that are ready to be rented.Keywords: Application, Online Rental, Agricultural Land / Rice Fields, UCD..